2003
DOI: 10.1557/jmr.2003.0237
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of thick YBa2Cu3O7−δ films on improved rolling-assisted biaxially textured substrates

Abstract: The microstructural changes associated with the reduced dependence of critical current density (J c ) versus thickness of thick, epitaxial YBa 2 Cu 3 O 7−␦ (YBCO) films on rolling-assisted biaxially textured substrates (RABiTS) were investigated. Pulsed laser deposited YBCO films varying in thickness from 1.0 to 6.4 m on RABiTS with an architecture of Ni-3 at.% W/Y 2 O 3 /yttrium-stabilized-zirconia/CeO 2 /YBCO were prepared for cross-sectional transmission electron microscopy studies. Dramatic improvements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…This is in stark contrast to the TEM of the 3.0 m film on RABiTS with configuration CeO 2 /YSZ/CeO 2 /Ni shown in Fig. 4 where the CeO 2 cap layer was completely reacted with the YBCO layer 10,12,13 . This improved microstructure, assumed to be because of more suitable characteristics of the buffer layer stack with thick Y 2 O 3 seed layer, is certainly a contributing factor for the improved thickness dependence of J c observed in this study.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…This is in stark contrast to the TEM of the 3.0 m film on RABiTS with configuration CeO 2 /YSZ/CeO 2 /Ni shown in Fig. 4 where the CeO 2 cap layer was completely reacted with the YBCO layer 10,12,13 . This improved microstructure, assumed to be because of more suitable characteristics of the buffer layer stack with thick Y 2 O 3 seed layer, is certainly a contributing factor for the improved thickness dependence of J c observed in this study.…”
Section: Resultscontrasting
confidence: 74%
“… Cross‐sectional bright field transmission electron microscopy images of a 3.0 and 2.9 μm YBa 2 Cu 3 O 7−δ (YBCO) films on (a) CeO 2 /YSZ/CeO 2 /Ni (after Leonard et al 12,13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work by Foltyn and others has shown that these ''dead'' layers are not endemic of thick YBCO coated conductors, but instead dependent on the growth conditions. [8][9][10][11] In this letter, we report ion-milling studies on YBCO grown by the BaF 2 ex situ process on IBAD-YSZ buffered metal substrates. The details of the BaF 2 ex situ growth process 7,12 and preparation of IBAD-YSZ buffered metal tapes 13 are given elsewhere.…”
mentioning
confidence: 99%
“…Generally, at these extreme growth conditions, an unfavorable orientational relationship results between the native oxide and metal substrate, degrading the subsequent nucleation of crystalline oxide buffer layers. Although epitaxial growth of various oxide layers have been successfully achieved over the years by effectively controlling the surface conditions of metallic tapes [1], insulating interfacial metal-oxide formation during the subsequent deposition of (YBCO) films has not been completely prevented [2], [3]. Regarding a fully conductive architecture, this problem is a major concern since it causes a partial or total loss of electrical connection between the HTS layer and the underlying substrate material [4], [5].…”
Section: Introductionmentioning
confidence: 99%